Coverage scheduling algorithm of mobile sensor nodes for optimizing network lifetime - Haibo YANG; Yourong CHEN; Banteng LIU; Yunkai ZHU; Ziyi SU (Dianxin kexue)
In order to solve the coverage blind problem caused by deployment and failure of heterogeneous static sensor nodes,a coverage scheduling algorithm of mobile sensor nodes for optimizing network lifetime (CSA) was proposed.CSA considerd heterogeneous perceived radius of static sensor nodes and calculates the location of mobile sensor nodes based on the information of neighbor static sensor nodes.According to the location reported by static sensor nodes,coverage scheduling model was established.Heuristic solution method was proposed,to solve the scheduling model,and optimal location of mobile sensor nodes was obtained.The simulation results show that CSA can improve regional coverage and the number of survival static sensor nodes,improve network lifetime and reduce energy consumption of average static sensor nodes.Under certain conditions,CSA is better than Mno,MNode and MGrid algorithms.